Utility decrements associated with side effects in schizophrenia. (23rd September 2014) - Millier, A.; Amri, I.; Boyer, L.; Auquier, P.; Toumi, M.
Abstract: Objective: Most of the existing studies investigating the impact of schizophrenia on utility have focused on the different stages of the disease. The objective of this study was to describe and quantify the impact of treatment-related side-effects on utility in patients with schizophrenia, using data from an observational study. Methods: This study used data from the European Schizophrenia Cohort (EuroSC), a multi-center 2-year cohort study conducted in France, England, and Germany. The EQ-5D questionnaire was completed every 6 months, as well as the Subjective Side Effect Rating Scale, assessing patient distress over extrapyramidal symptoms (EPS), weight gain, sedation, and sexual dysfunction, used to assess whether or not the patient experienced the side-effect. At first a bivariate analysis was conducted to describe utility values with and without side-effects. Then, a random effects regression analysis was performed on utility, where random effects were controlled for repeated measures on the same subjects, with potential confounding factors. Finally, findings were compared with those of previous publications. Results: This sample consisted of 1208 patients with schizophrenia. At the baseline visit, the most reported side-effect was EPS (almost 60% of patients), followed by sedation and weight gain (∼50% of patients for each), and sexual dysfunction (almost 30% of patients). Significant association with severity of symptoms, functioning abilities, and utility were found. Patients reporting none of the studied side-effects had an average EQ-5D index score of 0.81, found to be higher than scores of patients reporting EPS (0.70), sexual dysfunction (0.67), sedation (0.70), or weight gain (0.72). The random effects model reported a utility decrement of 0.042 for EPS, 0.022 for weight gain, 0.022 for sexual dysfunction, and 0.019 for sedation. Although the external validation was difficult due to the different methods or definitions of the side-effects, as well as the paucity of data for weight gain, sedation and sexual dysfunction, the results were generally consistent with previous studies. Conclusion: This study aimed at quantifying the direct impact of main side-effects associated with antipsychotics on patients' utility. Results suggested a significant direct impact of side-effects, with EPS being the most impactful.